Safety of Amiodarone in Ventricular Arrhythmia in Patients Admitted in Bangabandhu Sheikh Mujib Medical University (University Heart Journal, 2021)
Background: Amiodarone is the most effective antiarrhythmic medications available today for the treatment of both atrial and ventricular arrhythmias. It is an iodinated benzofuran derivative with demonstrated efficacy against a range of cardiac arrhythmias, including atrial fibrillation, paroxysmal supraventricular tachycardias, and life-threatening ventricular arrhythmias. Objective: To evaluation the status of amiodarone with therapeutic dose in Bangladeshi population. Materials and Methods: The quasi experimental study was conducted in the Department of Cardiology in Bangabandhu Sheikh Mujib Medical University (BSMMU), Shahbagh, Dhaka during April, 2019 to March, 2020 Patients got admitted in the Department of Cardiology, BSMMU, consecutive patients who had been treated with amiodarone for arrhythmia were included in this study. Patients without an amiodarone prescription were assumed and patients who will not give informed written consent were excluded in this study. Results: The most common adverse event was bradycardia or conduction disturbance (9.0%) followed by 4(2.2%) thyroid toxicity, 3(1.7%) hepatic toxicity, 2(1.1%) eye toxicity and 1(0.6%) pulmonary toxicity. In multi variable logistic regression, bradycardia or conduction disturbance, amiodarone daily dose (≥300 mg) and duration of amiodarone (>4 month) was found to be significantly (p4 month) was found to be significantly associated with adverse effects of amiodarone.University Heart Journal Vol. 17, No. 2, Jul 2021; 118-121